2014
DOI: 10.1155/2014/476123
|View full text |Cite
|
Sign up to set email alerts
|

Interfacial Properties of CZTS Thin Film Solar Cell

Abstract: Cu-deficient CZTS (copper zinc tin sulfide) thin films were grown on soda lime as well as molybdenum coated soda lime glass by reactive cosputtering. Polycrystalline CZTS film with kesterite structure was produced by annealing it at 500°C in Ar atmosphere. These films were characterized for compositional, structural, surface morphological, optical, and transport properties using energy dispersive X-ray analysis, glancing incidence X-ray diffraction, Raman spectroscopy, scanning electron microscopy, atomic forc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
4
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 34 publications
1
4
0
Order By: Relevance
“…The presence of excess Cu comes from the fluorescent signal, which is created by/due to the supporting copper grid. The results confirmed the stoichiometry of the nanopowders as Cu2ZnSnS4 [37][38][39].…”
Section: Resultssupporting
confidence: 74%
See 1 more Smart Citation
“…The presence of excess Cu comes from the fluorescent signal, which is created by/due to the supporting copper grid. The results confirmed the stoichiometry of the nanopowders as Cu2ZnSnS4 [37][38][39].…”
Section: Resultssupporting
confidence: 74%
“…The three characteristic reflexes of kesterite (2θ = 28.530, 47.329, and 56.175 degrees) are clearly visible. The fourth one (2θ =32.988 degree) is noticeable in the patterns from which it can be concluded that nanocrystals of kesterite were obtained [38][39][40]. Calculations based on the Scherrer method and FWHM confirms that the grain size is 5 nm [41].…”
Section: Resultsmentioning
confidence: 79%
“…From them Mo is found to be the most appropriate back contact material because of its inertness, high conductivity, stability at the processing temperature, low contact resistance, etc. The surface of the CZTS absorber layer has excellent contact with the Mo back contact which is helpful for decreasing the minority carrier recombination and providing a current path for minority carriers to reach the n-type material is used in solar cell (Muhunthan et al, 2014). A poor contact between Mo and CZTS which is a cause of reducing the efficiency of solar cell.…”
Section: Introductionmentioning
confidence: 99%
“…Many of the defects at the interface between kesterite and adjacent materials are created during the annealing process, due to the inter-diffusion of the components. Secondary phases can, therefore, be had, such as Cu 2 S near the CdS and ZnS / SnS 2 close to Mo, thus destroying the bands' alignment[23][24][25].Until now, the CdS is the most efficient buffer layer for kesterite based solar cells and CIGS, but there is a strong demand for the development of a Cd-free buffer layer, due to the toxicity of the Cd and its concerns regarding the long-term safety. Furthermore, the alignment of the band between the kesterite and CdS is not ideal, increasing recombination at the interface.…”
mentioning
confidence: 99%